CTIM-09. DOUBLE-BLINDED, PLACEBO CONTROLLED PHASE 2 STUDY OF ERC1671 IN RECURRENT GLIOBLASTOMA: VACCINE OVERALL SURVIVAL IN BEVACIZUMAB NAIVE AND BEVACIZUMAB RESISTANT PATIENTS. (9th November 2020) - Bota, Daniela; Taylor, Thomas; Kong, Xiao-Tang; Fu, Beverly; Hsu, Frank; Strik, Ankie; Schijns, Virgil; Stathopoulos, Apostolos
Abstract: ERC1671 is an allogeneic/autologous therapeutic vaccine – composed of whole, inactivated tumor cells mixed with tumor- cell lysates. The hypothesized action of ERC1671 is to potentiate the patients' immune system against the tumor. Goals of this ongoing, phase 2 study are to determine the safety and effectiveness (overall survival) of ERC1671 in combination with GM-CSF and cyclophosphamide as an add-on treatment to bevacizumab at the time of GBM recurrence. To date 22 recurrent bevacizumab-naïve rGBM patients have been randomized to ERC1671/GM-CSF/Cyclophosphamide + Bevacizumab or Placebo + Bevacizumab. Median age is 56.5 (33–74), 7 patients (32%) are female, and average KPS is 82.3 (70–100). Of the 22, two discontinued before completing one cycle of therapy and two remain on blinded treatment. Currently 18 patients are unblinded due to further progression: 8 were on vaccine and 10 on placebo. Five of those on placebo crossed to vaccine at progression. All but one of the 18 are now deceased. Median overall survival of unblinded patients randomized to ERC1671 + Bevacizumab (n = 8) is 264.5 days from the start of study treatment, compared to 182 days for those randomized to placebo + Bevacizumab who did not cross over (n = 5). Median overall survival of unblinded patients on vaccine at randomization or crossover is 328 days after first study treatment (n = 13). While sparse, the data to date suggest pre-treatment and maximal CD4+T lymphocyte count in the peripheral blood correlate with OS more strongly in the ERC1671 group than in the placebo group. First clinical results for toxicity show no difference in the distribution of AEs between the Vaccine and Placebo groups, with no Gr4/Gr5 AEs in either group. This phase 2 randomized, double-blinded study is ongoing, with the addition of one more site.